2021
DOI: 10.1177/20563051211010167
|View full text |Cite
|
Sign up to set email alerts
|

Reddit Gaming Communities During Times of Transition

Abstract: We studied the Reddit communities for three game franchises at the time of a new release in each franchise to see what the members of the Reddit community for the now-older game would do in terms of their community involvement and membership. Specifically, we sought to determine if community members transitioned to the community for a new game, leaving behind their established community devoted to the now-older game. Our main finding was that most people did not move to the new community, but instead remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Buntain and Golbeck (2014) studied community members on Reddit and found that people belong to one community, posting to one subreddit only. This mirrors findings in our previous work examining periods of transition in three different game franchises, including The Elder Scrolls (Bergstrom & Poor, 2021). Buntain and Golbeck’s study took place during times of relative stability for those online communities, and it provided the groundwork for our examination of relative instability for Reddit communities: studying user behavior around the time of a new release in a game series.…”
Section: Literature Reviewsupporting
confidence: 85%
“…Buntain and Golbeck (2014) studied community members on Reddit and found that people belong to one community, posting to one subreddit only. This mirrors findings in our previous work examining periods of transition in three different game franchises, including The Elder Scrolls (Bergstrom & Poor, 2021). Buntain and Golbeck’s study took place during times of relative stability for those online communities, and it provided the groundwork for our examination of relative instability for Reddit communities: studying user behavior around the time of a new release in a game series.…”
Section: Literature Reviewsupporting
confidence: 85%
“…We must note that subculture reflected on in this study, Reddit, reflects a particular subculture of gaming (Bergstrom & Poor, 2021;Proferes et al, 2021) and hence may not be reflective of more casual gaming communities where a person "would not describe herself as a gamer" (Vanderhoef, 2013, para. 9).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we are demonstrating the nature of discourse within one portion of the gaming community -namely, one comprised largely of younger, White, male players who frequently play violent video games (see Table 1). The Reddit sample, in other words, has benefit of circumscribing attention to a specific audience (Proferes et al, 2021) that tends to reflect the most devoted or "hardcore" gamers; however, this also means, conversely, that there will be less reflection of causal gamer communities reflected in the dialogue (Bergstrom & Poor, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Gaming culture on social media Bergstrom and Poor (2021) explore the fluidity and attachment of fan membership in Reddit gaming communities, by observing three subreddit communities dedicated to three different game franchises at the time of a new release or sequel to the franchise. The presumption is that fans and their consumption are deeply connected, to the extent that fans ought to want to migrate to the new subreddit community dedicated to the new release in the franchise.…”
Section: Previous Researchmentioning
confidence: 99%
“…Robards' (2018) emphasis on neotribalism in subreddits and how they are meticulous when it comes to content being relevant to the topic of the subreddit provides a deeper understanding of Bergstrom and Poor's (2021) findings on fluidity in fan commitment to subreddits. Robards (2018) suggests that Reddit users are interlocked in the sense that they are also members of other subreddits that are remotely related to the 'umbrella' subreddit, such as in the case of the subreddits dedicated to Bethesda's game franchise The Elder Scrolls, and Fallout.…”
Section: Previous Researchmentioning
confidence: 99%